2023
DOI: 10.1186/s13148-023-01535-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating NPTX2 methylation as a non-invasive biomarker for prognosis and monitoring of metastatic pancreatic cancer

María Victoria García-Ortiz,
Pablo Cano-Ramírez,
Marta Toledano-Fonseca
et al.

Abstract: Background Pancreatic cancer is the most lethal cancer with a dismal prognosis mainly due to diagnosis at advanced stage and ineffective treatments. CA19-9 levels and computed tomography (CT) imaging are the main standard criteria for evaluating disease progression and treatment response. In this study we explored liquid biopsy-based epigenetic biomarkers for prognosis and monitoring disease in patients with metastatic pancreatic ductal adenocarcinoma (mPDAC). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…However, post-therapy patients often show low methylation frequencies of RAS mutation and CA19-9, making them less ideal for tracking disease progression. In contrast, García-Ortiz et al found that NPTX2 exhibited the highest methylation frequency (87.5%) in cfDNA of mPDAC patients and maintained a higher level of methylation after treatment, starting from a baseline of 100% methylation frequency [85]. Additionally, higher plasma NPTX2 methylation levels were strongly correlated with shorter survival periods in these patients.…”
Section: Circulating Cell-free Dna and Methylationmentioning
confidence: 87%
“…However, post-therapy patients often show low methylation frequencies of RAS mutation and CA19-9, making them less ideal for tracking disease progression. In contrast, García-Ortiz et al found that NPTX2 exhibited the highest methylation frequency (87.5%) in cfDNA of mPDAC patients and maintained a higher level of methylation after treatment, starting from a baseline of 100% methylation frequency [85]. Additionally, higher plasma NPTX2 methylation levels were strongly correlated with shorter survival periods in these patients.…”
Section: Circulating Cell-free Dna and Methylationmentioning
confidence: 87%
“…It is noteworthy that the expression of GRIA4 is also much higher in E8 than E6 (Supplementary RNAseq data) as for NPTX2, suggesting some as-yet unidentified function for this ligand-receptor pair in hPSCs. NPTX2 is also a circulating biomarker of pancreatic cancer [69]. In glioblastoma NPTX2 has been shown to inhibit AKT which in turn represses NFKB activity [70].…”
Section: Plos Onementioning
confidence: 99%
“…In a recent study by our group, NPTX2 methylation levels was analyzed in plasma from 44 metastatic PDAC patients using ddPCR to evaluate its utility for prognosis and monitoring disease progression. Significantly, we demonstrated that the circulating NPTX2 methylation levels not only serve as a valuable prognostic biomarker but also offer a practical tool for monitoring metastatic PDAC patients [ 90 ]. Thus, correlations were observed between changes in NPTX2 methylation levels and disease progression as well as response to therapy, surpassing CA19-9 in predicting disease evolution in mPDAC patients.…”
Section: Analysis Of Cfdna Methylation Studies In Pancreatic Cancermentioning
confidence: 99%
“…Thus, correlations were observed between changes in NPTX2 methylation levels and disease progression as well as response to therapy, surpassing CA19-9 in predicting disease evolution in mPDAC patients. Moreover, in many cases, an elevation in circulating NPTX2 methylation levels preceded the detection of disease progression by CT imaging [ 90 ].…”
Section: Analysis Of Cfdna Methylation Studies In Pancreatic Cancermentioning
confidence: 99%